"We're Almost Guests in Their Clinical Care": Inpatient Provider Attitudes Toward Chronic Disease Management. Issue 3 (1st March 2017) - Blecker, Saul; Meisel, Talia; Dickson, Victoria Vaughan; Shelley, Donna; Horwitz, Leora I.
Abstract : BACKGROUND: Many hospitalized patients have at least 1 chronic disease that is not optimally controlled. The purpose of this study was to explore inpatient provider attitudes about chronic disease management and, in particular, barriers and facilitators of chronic disease management in the hospital. METHODS: We conducted a qualitative study of semi‐structured interviews of 31 inpatient providers from an academic medical center. We interviewed attending physicians, resident physicians, physician assistants, and nurse practitioners from various specialties about attitudes, experiences with, and barriers and facilitators towards chronic disease management in the hospital. Qualitative data were analyzed using constant comparative analysis. RESULTS: Providers perceived that hospitalizations offer an opportunity to improve chronic disease management, as patients are evaluated by a new care team and observed in a controlled environment. Providers perceived clinical benefits to in‐hospital chronic care, including improvements in readmission and length of stay, but expressed concerns for risks related to adverse events and distraction from the acute problem. Barriers included provider lack of comfort with managing chronic diseases, poor communication between inpatient and outpatient providers, and hospital‐system focus on patient discharge. A strong relationship with the outpatient provider and involvement of specialists were facilitators of inpatient chronic disease management. CONCLUSIONS: Providers perceived benefits to in‐hospital chronic disease management for both processes of care and clinical outcomes. Efforts to increase inpatient chronic disease management will need to overcome barriers in multiple domains.